Influence of Police Response Time and Investigative Practices on Homicide Case Clearance Rates in Kajiado West Sub County, Kajiado County, Kenya - Wario, Kalla Ibrahim; Musumba, George; Gathoni, Benson (Journal of Public Policy and Administration, 2025)
Purpose: This study examines the influence of police response time and investigative practices on homicide case clearance rates in Kajiado West Sub County, Kenya. Police response time is crucial for securing crime scenes, preserving evidence, and identifying suspects, while investigative practices such as forensic analysis, witness collaboration, and crime scene management play a significant role in case resolution. Methodology: The study employed a descriptive research design, utilizing both primary and secondary data collected from 109 police officers through structured questionnaires and official crime records. Data analysis was conducted using SPSS Version 24.0, incorporating descriptive and inferential statistics, including multiple linear regression analysis. Findings: Findings reveal that police response time significantly impacts homicide case clearance, with a strong correlation (r = 0.734, p < 0.01) and 53.9% of clearance rate variance explained by response time. Investigative practices also have a significant impact (r = 0.746, p < 0.01), explaining 55.6% of the variance in homicide clearance rates. Regression analysis confirms that improving response time (B = 0.596, p = 0.000) and investigative practices (B = 0.599, p = 0.000) significantly enhance clearance rates. Unique Contribution to Theory, Practice and Policy: To enhance homicide case clearance in Kajiado West Sub County, police response time should be reduced to below 30 minutes by increasing patrol vehicles and upgrading dispatch systems.